Cost Accounting and Productivity, the Use and Practice of Cost Accounting in the U.S.A Report by a Group of European Experts (book). - Vance, Lawrence L. (The Accounting Review, 1953)
Reviews the book "Cost Accounting and Productivity, the Use and Practice of Cost Accounting in the U.S.A."